Monopolistic Competition, Trade and Endogenous Spatial Fluctuations - Gianmarco Ottaviano (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
This paper investigates the possibility of endogenous fluctuations in the international distribution of economic activities in the presence of increasing returns, monopolistic competition, trade and convex adjustment costs. Differently from the existing literature, it does not allow for any local productive externalities. Using a 2-country dynamic general equilibrium model, it derives necessary and sufficient conditions for the existence of self-reinforcing relocation processes. It shows that the occurrence of multiple equilibria and endogenous fluctuations is associated with a high degree of increasing returns to scale as well as low trade and adjustment costs. Under such circumstances relocation processes are driven by self-fulfilling expectations.
Keywords: 330